“Determinación de parámetros tecnológicos para la elaboración de macerado de uva (uvachado) variedad borgoña negra (vitis labrusca)” - Archenti Viena, José (2005)
Results of present study puts on manifestation the incorporation of grape as a suitable raw material, for elaboration of macerated grape or 'uvachado', using like main intake the rum; through which established technological parameters that guarantee the conservation of macerated grape during its storage. Categorized grape as a suitable raw material, presents a ripeness index of 14.5 respectively. Like processing periods for elaboration of macerated grape, are emphasized: harvest, transportation, reception, weighed, desbunched by hand, washed, scalded, macerated, filtered and bottled. Estimating on each of periods the conditions and parameters referred like good practices on work and technological improvement: adequate selection of grape bunch, separation on it, washed with water and scalded with water at 50°C per minute, continuing with period of maceration in rum at 44°GL and 15ºC with a period of 10 days and starting from tenth first day on. In solutions comprehended by rum and inverted sugar at 60ºBrix to osmotic equlibrium, being these very important, treating of first as a destruction method of microorganisms during ten days and second in stabilization of components between grape and solution of maceration, referred by concentration of sugar, pH, acidity and alcoholic grade. Determining like a maceration time for osmotic equilibrium between macerated tissue and maceration solution of 60 days, depending on ripeness index of raw material, for reaching to: soluble solids concentration of: 29ºBrix, pH 4.0, acidity 0.24 and alcoholic grade at 20ºGL, respectively.